Comparison of Frozen and Final Pathology Results in Patients Operated for Endometrial Hyperplasia - Gonca Turker Ergun; Ugurcan Zorlu; Burak Elmas; Bengü Nur Baris Akcan; Gul Kurtaran; Kadir Cetinkaya; Melike Doganay (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Our study aimed to determine the frequency of endometrial cancer in patients undergoing surgery with a diagnosis of endometrial hyperplasia and to evaluate the concordance between preoperative diagnosis, frozen section examination, and final pathology results.